Nanoengineered Gd3Al2Ga3O12 Scintillation Materials with Disordered Garnet Structure for Novel Detectors of Ionizing Radiation - Korzhik, Mikhail; Alenkov, Vladimir; Buzanov, Oleg; Fedorov, Andrei; Dosovitskiy, Georgy; Grigorjeva, Larisa; Mechinsky, Vitaliy; Sokolov, Peter; Tratsiak, Yauhen; Zolotarjovs, Aleksejs; Dormenev, Valery; Dosovitskiy, Aleksei; et al. (Wiley-VCH Verlag, 2019)
The search for engineering approaches to improve the scintillation properties of Gd3Al2Ga3O12 crystals and enable their production technology is of current interest. This crystal, while doped with Ce, is considered a good multi‐purpose scintillation material for detecting gamma‐quanta and neutrons. It is observed that co‐doping with Mg affected intrinsic defects in the crystal structure that create shallow electronic traps. Other point structure defects, which are based on local variations of the crystal stoichiometry, are significantly diminished by use of a co‐precipitated raw material. Nano‐structuring of the raw material enables production of a homogeneous precursor mixture for growing a crystal with minimal evaporation of Ga from the melt. The demonstrated nano‐engineering approach increased the light yield from the crystal by approximately 20%, enabling its applications in well logging.
The authors are grateful to Baker Hughes a GE Company for support of this activity. This work has also been supported by grant N14.W03.31.0004 from the Government of the Russian Federation.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; co-precipitation; disordered crystal; luminescence; multicomponent garnet; nanoengineering; scintillators